PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN DI BANK SYARIAH MANDIRI SIDOARJO - D (Jurnal Ekonomi dan Bisnis, 2020)
The quality of service in a banking service company is very important from the consumer's point of view. The purpose of this study was to determine and explain the effect of service quality on customer satisfaction at Bank Syariah Mandiri Juanda in Sidoarjo. This quantitative descriptive study uses a survey method by distributing questionnaires to respondents. Some of the tests carriedout were the validity and reliability of the questionnaire, the classical assumption test, and the statistical test (simple linear regression). The results of the regression analysis show that service quality has a significant effect on customer satisfaction.